«Faciem morbo»: personal characteristics of patients with Parkinson’s disease - V. A. Bogacheva; D. V. Zakharov; V. A. Mikhailov; V. V. Bocharov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The psychological characteristics of patients with akinetic-rigid andtrembling forms of Parkinson’s disease were compared. It was revealed that regardless of the form of the disease, all patients with PD are characterized by a decrease in their perception of their social reputation, attractiveness, popularity, respect for others, as well as the ability to achieve their goals; unsociability, poor self-giving ability, poor imagination, and lack of long-term attachments. Only patients with the akinetic-rigid form arecharacterized by docility, obedience, complaisance, patience, distrust, and detachment from other people. Most of the patients we examined with PD are highly likely to perceive stressful situations as threatening and alarming.